Kafe Baca Yang Ramah Pada Penyandang Disabilitas - Nur'aini, Nur'aini (Universitas Negeri Padang, 2022)
The purpose of writing this article is to find out an overview of reading cafes that are friendly to people with disabilities. Literature review as a method of writing this article by looking for relevant theoretical references from various sources of books and journal articles. Sources of data for this writing are compiled from several sources of documents, scientific journals and textbooks. Collecting data from observations of various information contained in journals, books and serials related to topics related to reading cafes that are friendly for disabilities. This writing data analysis uses descriptive narrative. The result of writing this article is necessary to pay attention to facilities that are easily accessible for people with disabilities. Starting from disabilities that have visual impairment, deafness, reading difficulties, physical and cognitive disorders. In addition, the facilities, policies, services and programs provided for persons with disabilities will be able to develop and enhance creativity, achievement and more productive self-development and to create a reading cafe that is friendly to persons with disabilities and must pay attention to access to information that is in accordance with the needs of persons with disabilities.